Geometria e simetrias do emaranhamento - Braga, Helena Carolina (2011)
In the present work we present a geometric method to identify and measure the degree of entanglement of a two-qubit state. It is based on writing a map of the system state, from a non-unitary transformation. By introducing new parameters for such 4X4 matrix, the product of eigenvalues, two by two, acquire the form of squared 4D distances, having a Minkowski metric. If the squared distance is of the kind timelike, i.e.non-negative, the two-qubit system is separable. Otherwise, if it is spacelike, namely, the squared distance is negative, the two qubits are entangled. Besides being invariant by unitary transformations on the system state, the distances can be represented in a hyperbolic parameterized phase space, allowing a suitable graphic representation, i. e., in a phase space where the system trajectories can be drawn. The method is extended to a large class of 4x4 positive matrices having at most seven independent parameters, the D-7 manifold class. Using group theory methods we classify these states according to the symmetries of seven generators, where one of them commutes with the others. We illustrate the method and the theory by presenting several two-qubit systems found in the literature. We also study the symmetry breaking and the criticality in two-qubit Heisenberg Models, looking for signatures of quantum phase transitions in terms of the squared distances as well as in its derivatives.